2021
DOI: 10.37349/etat.2021.00046
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the study of cancer metastasis and calcium signaling as potential therapeutic targets

Abstract: Metastasis is still the primary cause of cancer-related mortality. However, the underlying mechanisms of cancer metastasis are not yet fully understood. Currently, the epithelial-mesenchymal transition, metabolic remodeling, cancer cell intercommunication and the tumor microenvironment including diverse stromal cells, are reported to affect the metastatic process of cancer cells. Calcium ions (Ca2+) are ubiquitous second messengers that manipulate cancer metastasis by affecting signaling pathways. Diverse tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 217 publications
0
4
0
Order By: Relevance
“…Since calcium works as a second messenger, dysregulation of calcium homeostasis is associated with different diseases, including different types of cancer, muscular dystrophy, and diabetes, which are also involved in cell wound repair (Ahn et al, 2017; Arruda and Hotamisligil, 2015; Cui et al, 2021; Levy, 1999; Monteith et al, 2017; Xu et al, 2018). Consistent with this, intracellular calcium levels from different sources in the disease conditions are known to enhance or impair cell wound repair in a context-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Since calcium works as a second messenger, dysregulation of calcium homeostasis is associated with different diseases, including different types of cancer, muscular dystrophy, and diabetes, which are also involved in cell wound repair (Ahn et al, 2017; Arruda and Hotamisligil, 2015; Cui et al, 2021; Levy, 1999; Monteith et al, 2017; Xu et al, 2018). Consistent with this, intracellular calcium levels from different sources in the disease conditions are known to enhance or impair cell wound repair in a context-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…42 Metastasis and invasion of tumor cells are 2 main causes of tumor recurrence and chemoradiotherapy resistance. 43 Pinostrobin inhibits the migration of breast cancer cells by inhibiting focal adhesion formation and cell adhesion. 11 Tumor cells can avoid excessive DNA damage and reduce apoptosis through the G2 checkpoint.…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…Ca 2+ signalling plays an important role in the regulation of all these processes physiologically, and is therefore one of the potential regulators of metastatic cascades as well. Several studies have reported the role of Ca 2+ channels and increasing cytosolic Ca 2+ levels in cancer cell metastasis, and therefore various pharmacological agents (Ca 2+ channel inhibitors/blockers) have been suggested as a potential pharmacological strategy against metastasis formation (Cui et al., 2021). Despite these efforts, the role of Ca 2+ transporters, especially PMCA4, has only recently started to attract considerable interest.…”
Section: Introduction: Cell Migration and The Role Of Ca2+ Signallingmentioning
confidence: 99%